Identification of dominant global and local modes behind dynamic stiffness valleys in BIW structures via modal contribution and ESE - Mingsheng Wang; Wendi Wang; Tao Chen; Xiangwei Lu; Xuelian Yi (PLoS ONE, 2025)
This study proposes a novel methodology that integrates modal contribution analysis with Element Strain Energy (ESE) distribution to identify the dominant modes causing dynamic stiffness variations in Body-in-White (BIW) structures. As Noise, Vibration, and Harshness (NVH) performance becomes increasingly critical in automotive design, accurately identifying the sources of dynamic stiffness deficiencies in the early design stages is imperative. This research addresses a significant gap in existing literature, where traditional methods struggle to distinguish between global and local modes in high-frequency, dense modal environments. By systematically analyzing the impact of both global and local modes on dynamic stiffness at key vehicle body connection points, our findings demonstrate the critical importance of prioritizing higher-frequency modes with localized strain energy concentrations for early-stage structural analysis. The proposed approach effectively tackles challenges such as modal overlap and frequency discrepancies, thereby enhancing the precision of NVH diagnostics and providing a reliable framework for targeted structural optimization. Consequently, this work offers a substantial advancement in the understanding and enhancement of NVH performance in automotive body structures, contributing to more efficient and effective design processes.